قياس سعة الذاكرة قصيرة المدى لدى اطفال الرياض (Journal Of Educational and Psychological Researches, 2014)
The research aims to measure short-term memory capacity for the kindergarten children, the researcher has prepared measure short-term memory capacity test for (4-6  years) Consists of two parts, Auditory memory, consisting of (4) items And visual memory, consisting of (5) items. Selected sample (340) children from for the kindergarten children.      To verify the skills validity adopted the skills, Researcher used indicators which are logical  validity , Through the items  experts' examining logically. and construction validity through som of the indicators which are the discriminatory power of the items.    In order to prospect the constancy the researcher adopted of  Test and re-test .The results showed that short-term memory capacity for the kindergarten children reached (4.2288) any (4) units or elements It is less than the memory capacity of the older adult individuals (7). units or elements.